APLIKASI DOSIS PUPUK VERMIKOMPOS PADA BIBIT TANAMAN GAHARU (Aquilaria malaccensis Lamk) - Munawir ' '; Soempoerno ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The study aims to get a dose ofvermicompostfertilizer suitablefor the growth ofplant seedsgaharu (Aquilaria malaccensisLamk). This study lasted from May toAugust 2015 at Plants in the Laboratory of the Faculty of Agriculture, University of Riau Simpang Village New District of Tampan Pekanbaru. Research carried out for 3 months from May to August 2015. This study was conducted experimentally by using completely randomized design consisting of 5 treatments and 3 replicates in order to obtain 15 units of study.   The treatment given is the use of multiple doses of vermicompost fertilizer that V0 = 0 g / polybag, V1 = 11,25 g / polybag, V2 = 15 g / polybag, V3 = 18,75 g / polybag and V4 = 22,5 g / polybag. The data obtained were statistically analyzed using analysis of variance were significant and continued with the smallest value different test (BNT) at 5%. Parameters measured were plant height increment (cm), in the number of leaves (pieces), stem diameter increment (cm), aloe plant dry weight (g) and the ratio of crown roots (g). The results showed that vermicompost fertilizer dose of 22.5 g /polybag shows the effect on plant height increment parameter, in the number of leaves, increase stem diameter, plant dry weight and ratio root crown. Giving a dose of 22.5 g / polybag is the best dosage to improve plant growth gaharu (Aquilaria malaccensis Lamk). Keywords :Aquilaria malaccensis Lamk and Vermicompost